1996
DOI: 10.21273/jashs.121.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Mobility, and Filtration of Metolachlor in Container Media

Abstract: Adsorption, mobility, and filtration ability of organic media toward metolachlor were evaluated in a series of laboratory experiments. Experimental variables included media type, metolachlor concentration, and equilibration time. Adsorption isotherms were determined by applying the log form of the Freundlich equation. Mobility was evaluated using glass columns filled with media, which were then surface spiked with metolachlor and then leached daily for 10 consecutive days. Peat, pine bark, combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Bulk densities were 0.16, 0.17, 1.5 gÁcm -3 for pine bark, hardwood bark, and sand, respectively. The results of analysis were similar to other reports for pine bark (Brown and Pokorny, 1975;Daniels and Wright, 1988;Grey et al, 1996;Simmons and Derr, 2007) and hardwood bark (Brake et al, 1992). The sand was 90% sand, 0% silt, and 10% clay.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Bulk densities were 0.16, 0.17, 1.5 gÁcm -3 for pine bark, hardwood bark, and sand, respectively. The results of analysis were similar to other reports for pine bark (Brown and Pokorny, 1975;Daniels and Wright, 1988;Grey et al, 1996;Simmons and Derr, 2007) and hardwood bark (Brake et al, 1992). The sand was 90% sand, 0% silt, and 10% clay.…”
Section: Resultssupporting
confidence: 89%
“…Pine bark, hardwood bark, and sand macropore space were 54%, 65%, and 6%, whereas waterholding capacity was 79%, 134%, and 30%, respectively. Simmons and Derr (2007) reported similar pore space volumes for pine bark and Grey et al (1996) reported similar gravimetric waterholding capacity for pine bark. Hardwood bark was very absorptive to water.…”
Section: Resultsmentioning
confidence: 81%
“…as a cost-efficient substitute for activated carbon as adsorbent for anthropogenic contaminants, e.g., dye (Leitch et al, 2006), phenol (Vázquez et al, 2007), heavy metal ions (Vázquez et al, 1994) and metolachlor (Grey et al, 1996). Gendrault et al (2005) observed high adsorption of atrazine onto pine bark.…”
Section: Substrate Selectionmentioning
confidence: 99%
“…The adsorption of fungicides to peat and the degradation decreased the concentration of both fungicides in leachates as time passed. In laboratory experiments, adsorption of herbicides, oxadiazon and metolachlor, was over 90% in peat medium (Wehtje et al 1993, Grey et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the characteristics of the active ingredient, the properties of the growing medium and cultural practices in container production influence the fate of the active ingredient in the nursery environment (Landis et al 1991, Torstensson & Stenstrom 1995. Only a few studies have investigated the leaching of herbicides from media used in container nurseries (Wehtje et al 1993, Mahnken et al 1994, Grey et al 1996, but to the authors' knowledge there are no published results about leaching of pesticides during actual production of container forest seedlings. Therefore, the objective of this study was to determine possible leaching of propiconazole and chlorothalonil from peat growing medium into the ground during commercial production of container-grown Scots pine seedlings.…”
Section: Introductionmentioning
confidence: 99%